2012
DOI: 10.1002/ctpp.201100053
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐Electrode Distance and Breakdown Voltage in Low Pressure Argon Discharges

Abstract: This work deals with the Paschen law in electrical breakdown of gases at pd values around the Paschen minimum. From the Townsend model, it is possible to deduce theoretical forms of the coefficients in Paschen's law, of which our calculated values are in the range of the tabulated values from the literature. These formulae show that the breakdown voltage must be influenced by the inter‐electrode distance, while the product pd remains a key parameter. This is confirmed by the Paschen curves measured in an argon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…In a wide range of these implementations, the glow discharge occurs between two electrodes located in the discharge oversize, incomparably to systems of inductively coupled or microwave excited. Hence, the reactor design and optimization, including the inter-electrode distance, is one of the key issues in the technical practice [5]. A glow discharge is characterized by its distinctive regions between the cathode and the anode electrodes across the tube.…”
Section: -Introductionmentioning
confidence: 99%
“…In a wide range of these implementations, the glow discharge occurs between two electrodes located in the discharge oversize, incomparably to systems of inductively coupled or microwave excited. Hence, the reactor design and optimization, including the inter-electrode distance, is one of the key issues in the technical practice [5]. A glow discharge is characterized by its distinctive regions between the cathode and the anode electrodes across the tube.…”
Section: -Introductionmentioning
confidence: 99%
“…The latter process makes the breakdown a selfsustaining electric discharge. In 1889, Paschen presented a law stating that the breakdown voltage is dependent on the product of the gas pressure and the space between the two electrodes as V b = f (Pd) [9,10]. In 1915, Townsend introduced two quantities to explain the current growth through the gas discharge known as the first Townsend ionization coefficient () and second Townsend emission coefficient (γ) [11].…”
Section: Introductionmentioning
confidence: 99%
“…where A and B are constants depending on the gas properties [10]. The value of Pd at which the minimum breakdown voltage occurs is:…”
Section: Introductionmentioning
confidence: 99%
“…Low-pressure gas breakdown is a function of the product of the gas pressure, the electrode gap spacing and the electrode surface condition as well. 4,5 Especially for high voltage solar arrays, outgassing plays a critical role in arc inception, in which outgassing helps to generate the initial plasma near the metal-dielectric junctions, and it's also demonstrated that arcing rate decreases after fully outgassing. [6][7][8] The obvious worry associated with the local gas environment is the difficulty in determining exactly the electrical breakdown characteristics for the gas species.…”
Section: Introductionmentioning
confidence: 99%